Legal Analysis and Case Studies On Conspiracy In Narcotics Crimes - Budiyanto, Budiyanto (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
This research aims to determine the offense of Criminal Conspiracy in Narcotics Crimes and to determine the basis of the judge's considerations in Decision Number 120/Pid.Sus/2023/PN Mks. This research uses normative legal research methods, and a discussion of this thesis is written as a legal research method. The use of normative research methods in research efforts and writing this thesis is based on the suitability of theory with the research methods required by the author. The results obtained are presented descriptively. 1.) Law Number 35 of 2009 regulates sanctions against narcotics abusers who commit narcotics crimes. Dangerous Conspiracy is the act of two or more people conspiring to commit, carry out, assist, participate in, order, recommend, facilitate, provide consultation, become members of a narcotics crime organization, or organize narcotics crimes. Any person who offers to sell, sells, buys, receives, becomes an intermediary in buying and selling, exchanges, or delivers Class I Narcotics without right or against the law shall be punished with life imprisonment, a minimum imprisonment of five years, and a maximum imprisonment of twenty years, and fines of one billion rupiahs and ten billion rupiahs. 2) The Panel of Judges in case no. 120/Pid.Sus/2023/PN Mks sentenced the defendant to six years in prison and a fine of Rp. 1,000,000,000.00 for conspiracy to buy and sell narcotics class I. The defendant's actions were considered aggravating because he rejected the government's efforts to eradicate narcotics and drug abuse, as well as reducing his polite attitude at trial. The defendant has never been convicted; this shows that the defendant's actions are in line with the goals of the criminal justice system.